In vivo visualisation of different modes of action of biological DMARDs inhibiting osteoclastic bone resorption. Issue 8 (28th April 2018) - Matsuura, Yoshinobu; Kikuta, Junichi; Kishi, Yuika; Hasegawa, Tetsuo; Okuzaki, Daisuke; Hirano, Toru; Minoshima, Masafumi; Kikuchi, Kazuya; Kumanogoh, Atsushi; Ishii, Masaru
Abstract : Objectives: Osteoclasts play critical roles in inflammatory bone destruction. Precursor cell migration, cell differentiation, and functional cell activation are all in play. Biological disease-modifying antirheumatic drugs (DMARDs) have been shown to significantly inhibit both bone erosion as well as synovitis, although how such agents reduce osteoclastic bone destruction in vivo has not been fully explained. Here, we used an intravital time-lapse imaging technique to directly visualise mature osteoclasts and their precursors, and explored how different biological DMARDs acted in vivo . Methods: Lipopolysaccharide (LPS) was injected into the calvarial periosteum of fluorescent reporter mice to induce inflammatory bone destruction. Time-lapse imaging was performed via intravital multiphoton microscopy 5 days after LPS injection. Biological DMARDs, including monoclonal antibodies (mAbs) against the interleukin (IL) 6 receptor (IL-6R) and tumour necrosis factor α (TNFα), or cytotoxic T-lymphocyte-associated protein 4 (CTLA4)-Ig, were intraperitoneally administered at the time of LPS injection. We determined CD80/86 expression levels in mature osteoclasts and their precursors by flow cytometry, quantitative PCR and immunohistochemistry. Results: Of the biologicals tested, anti-IL-6R and anti-TNFα mAbs affected mature osteoclasts and switched bone-resorbing osteoclasts to non-resorbing cells. CTLA4-Ig had no action on mature osteoclasts but mobilised osteoclast precursors, eliminating their firm attachment to bone surfaces. In agreement with these results, CD80/86 (the target molecules of CTLA4-Ig) were prominently expressed only in osteoclast precursor cells, being suppressed during osteoclast maturation. Conclusions: Intravital imaging revealed that various biological DMARDs acted at specific therapeutic time points during osteoclastic bone destruction, with different efficacies. These results enable us to grasp the real modes of action of drugs, optimising the usage of drug regimens.